Interpreting Food Images in Gina S. Noer's Films (Cinematology: Journal Anthology of Film and Television Studies, 2024)
In an evolution of cinematography, the depiction of food in film serves not only as a visual element but also as a means of conveying artistic messages. This research aims to comprehend how Gina S. Noer, an Indonesian filmmaker, imbues meaning into the depiction of food in her works. Through an analysis of her films, including “Dua Garis Biru” and “Like and Share” this study explores various semiotic analysis employed by Noer to communicate the underlying significance of food imagery. The study utilizes film analysis and semiotics to interpret the use of food as symbols and metaphors within the context of the stories presented by Gina S. Noer. This research contributes to a deeper understanding of the use of food imagery in a cinematic context, particularly within the works of Gina S. Noer. These insights may serve as a foundation for further exploration into how visual elements such as food can enhance the audience experience and deepen the narrative significance in the context of Indonesian cinema.